How knowledge time influenced anxiety, depression, stress and quality of life levels in patients suffering from Crohn disease: a cross-sectional multicenter study: Anxiety, depression, stress and quality of life levels in patients suffering from Crohn disease - Vitale, Elsa; Lupo, Roberto; Artioli, Giovanna; Lezzi, Alessia; Secondo, Daniela; Mignone, Annarita; Calabrò, Antonino; Carvello, Maicol; Caldararo, Cosimo; Lezzi, Pierluigi; Scupola, Giovanni Maria; Zacchino, Simone; et al. (Acta Biomedica Atenei Parmensis, 2023)
Background and aim of the work. The diagnosis of Crohn Disease (CD) represents a turning point in the life of patients, which inevitably marks them. The present study represents a direct "feed-back" from patients suffering from Crohn disease, in order to reveal how the diagnosis of CD changed lifestyles and psychological conditions in their patients. Methods. An observational, cross sectional, online, snowball sampling study was conducted through participants suffered from CD and belonged to social networks and Facebook groups. For each participant, sampling characteristics, a series of lifestyle habits Before to After the diagnosis of CD and anxiety, depression, and stress conditions were investigated. Results. A total of 785 participants agreed to participate. As Participants underwent significant challenges in their lifestyles after the CD diagnosis (p<0.001), specifically their reduced their smoking habits, alcohol and drugs intakes and also their diets both in high sugar and fatty compositions. Anxiety and stress levels were not statistical different among participants according to years of the knowledge of their CDs. Meanwhile, as regards depression condition, significantly higher levels were recorded among participants who knew their CD until 5 and 25 years, respectively (p=0.031). Conclusions. From the study emerges several aspects of quality of life compromised, a fact supported by the analysis of psychophysical sequelae, which allowed to lay the groundwork for further studies, studying the comorbidity of this disease with other factors. Future randomized controlled trials should deepen the correlation between eating disorders and CD, a link little explored in the literature.